Antibacterial packaging material as well as preparation method and application thereof

Through biological enzymes, seafood packaging materials with antibacterial and antioxidant properties have been developed, which solves the problems of seafood spoilage and microbial contamination, and achieves the extension of shelf life and improves food safety. Effect.

CN119507265APending Publication Date: 2025-02-25安徽粤智徽源生物科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311074298.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-24
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Seafoods are susceptible to oxidation and microbial contamination, leading to spoilage and health risks, and existing packaging materials are difficult to effectively prevent these problems.

Method used

By promoting the cross-linking modification of phenolic substances and fibers by biological enzymes, eucalyptus mechanical pulp paper or packaging material with antibacterial and antioxidant properties is prepared.

Benefits of technology

This material can effectively inhibit the growth of Vibrio, degrade nitrites, extend the shelf life of seafood, improve the freshness and safety of food, and reduce chemical pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119507265A_ABST
    Figure CN119507265A_ABST
Patent Text Reader

Abstract

The invention provides an antibacterial packaging material as well as a preparation method and application thereof, specifically, phenolic substances are successfully cross-linked to a main component unit, namely eucalyptus mechanical pulp, of a seafood packaging material by virtue of the action of biological enzyme, so that the cross-linked eucalyptus mechanical pulp obtains unexpected antibacterial and antioxidant properties, and the antibacterial packaging material has the advantages of being simple in preparation process, low in cost and good in application prospect. Furthermore, paper or a packaging material prepared from the eucalyptus mechanical pulp has the functional characteristics of being capable of degrading nitrite, resisting vibrio and resisting oxidation, and has certain practical values on preservation, quality improvement, inhibition of growth of harmful microorganisms and oxidation resistance when being used as a packaging material of marine products; the invention belongs to a completely innovative scheme in the field of seafood packaging materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of packaging material preparation, and in particular to an antibacterial packaging material and a preparation method and application thereof. Background Art

[0002] my country is the largest producer of seafood. Fish, shrimp and other seafood products are rich in nutrition and are popular among consumers. The deterioration of seafood is mainly caused by high lipid oxidation. For example, fish contains a large amount of unsaturated fatty acids, which are easily oxidized by reactive oxygen free radicals. Moreover, seafood is easily contaminated by exogenous Vibrio. In turn, human contact with seafood contaminated by Vibrio can cause serious wound infection and even primary sepsis. Anti-Vibrio packaging materials can block this potential pathogenic risk. Seafood is rich in protein. Improper storage or excessive storage for a long time can easily produce a large amount of nitrite, which may induce cancer. Ingestion of 0.3-0.5g of nitrite can cause methemoglobin poisoning or even death. In addition, seafood contains some easily oxidized ingredients, which will reduce the nutrition of food after oxidation and may even be harmful to the human body. Therefore, how to give packaging materials antioxidant properties is beneficial to maintaining the quality of seafood and protecting the health of consumers.

[0003] Surface cross-linked polymer modification is another important technical approach to improve the quality of mechanical pulp fibers and expand product functions. Based on the research and innovation that the inventors have done in the cross-linking of enzyme-catalyzed phenolic substrates with mechanical pulp lignin, how to explore and change the physical properties of pulp raw fibers such as hydrophilicity / hydrophobicity and binding force to improve fiber quality is an important research and innovation direction. In the prior art, for example, foreign scholars Garajová et al. used a laccase / 1-hydroxybenzotriazole (HBT) system to treat spruce TMP, oxidizing alcohol-soluble phenolic compounds in the fiber to oligomerize it, and HBT also polymerized with these phenolic compounds. After the reaction, the swelling of the fiber was reduced by 10%, and the tensile strength was increased by more than 1 times. When the oligomerization level was further increased (degree of polymerization>4), the hydrophobicity of the fiber was significantly improved. After enzyme-catalyzed polymerization and grafting of phenolic substances, new functions may be given to fibers. Fillat et al. used laccase to graft syringaldehyde, acetosyringone and p-coumaric acid onto unbleached flax fibers, which can significantly inhibit the activity of Staphylococcus aureus, Pseudomonas aeruginosa and Klebsiella pneumoniae. In particular, the inhibition rate of acetosyringone grafted pulp on Pseudomonas aeruginosa reached more than 97%. It can be seen that enzyme-catalyzed cross-linked polymer modification is of great significance for solving the problem of single function of mechanical pulp fiber products, broadening its application range, improving its application value, or developing new products. In addition, in the prior art, there are also reports on adding antioxidants such as carvacrol, gallic acid and clove oil to packaging. For example, scholars Yuan et al. added carvacrol to chitosan film, and the scavenging rate of DPPH free radicals can reach 85%. Scholars Xiong et al. prepared gelatin / chitosan / gallic acid / clove oil as antioxidant and antibacterial materials for salmon fillets, which can extend the shelf life by at least 5 days.

[0004] Therefore, based on the needs of seafood preservation and quality assurance, how to study the effect of phenolic grafting modification on increasing the anti-Vibrio, nitrite degradation and antioxidant activity of pulp, how to extract natural biological enzymes from natural plant materials, and study the role and application of enzymes in the above-mentioned grafting modification, and develop multifunctional packaging materials that can remove nitrite to extend the shelf life of seafood, protect the freshness and health of seafood, reduce other adverse health factors brought to users by the chemistry of packaging materials, and other burdens or pollution to the environment. This has important innovative significance and market prospects for those skilled in the art. Summary of the invention

[0005] In order to solve the many problems mentioned in the above background technology, the present invention successfully cross-links phenolic substances to the main component unit of seafood packaging materials - eucalyptus mechanical pulp by means of the action of biological enzymes, so that the cross-linked eucalyptus mechanical pulp obtains unexpected antibacterial and antioxidant properties, and then the paper or packaging material prepared from the eucalyptus mechanical pulp obtains the functional properties of degrading nitrite, resisting Vibrio and antioxidant. As a packaging material for seafood, it has certain practical value in preserving and improving quality, inhibiting the growth of harmful microorganisms and anti-oxidation, and is a completely innovative solution in the field of seafood packaging materials.

[0006] The technical solution adopted by the present invention is specifically as follows:

[0007] An antibacterial packaging material, characterized in that the antibacterial packaging material satisfies at least one of the following conditions:

[0008] (1) The water contact angle of the antibacterial packaging material is between 27.82±1.58° and 48.79±0.62°;

[0009] (2) The inhibition rate of the antibacterial packaging material on Vibrio fischeri after incubation for 30 minutes is greater than or equal to 21.2%;

[0010] (3) The inhibition rate of the antibacterial packaging material on Vibrio fischeri after incubation for 60 minutes is greater than or equal to 41.6%.

[0011] As a further improvement to the above scheme, the antibacterial packaging material is obtained by treating eucalyptus mechanical pulp with bio-enzyme-promoted phenols and fiber cross-linking modification, and the eucalyptus mechanical pulp is selected from MP pulp or PMP pulp.

[0012] As a further improvement to the above solution, the antibacterial packaging material satisfies at least one of the following conditions:

[0013] (1) When the eucalyptus mechanical pulp is MP pulp, the antibacterial packaging material prepared by subjecting it to biological enzyme-promoted phenolic and fiber cross-linking modification treatment has an inhibition rate of Vibrio fischeri greater than or equal to 18.0% after incubation for 30 minutes;

[0014] (2) When the eucalyptus mechanical pulp is PMP pulp, the antibacterial packaging material prepared by subjecting it to bio-enzyme-promoted phenolic and fiber cross-linking modification treatment has an inhibition rate of Vibrio fischeri greater than or equal to 26.4% after incubation for 60 minutes, wherein the PMP pulp of the eucalyptus mechanical pulp is PMP pulp that has been treated with bio-enzyme, chelate, and hydrogen peroxide bleaching in sequence.

[0015] As a further improvement to the above solution, the biological enzyme is specifically peroxidase extracted from natural palm plants.

[0016] As a further improvement to the above scheme, the phenols are specifically guaiacol, catechol, and gallic acid.

[0017] As a further improvement to the above scheme, when the phenol is selected as catechol, the biological enzyme is selected as peroxidase extracted from natural palm plants, and the antibacterial packaging material meets at least one of the following conditions:

[0018] (a) For the MP pulp of eucalyptus mechanical pulp, the antibacterial packaging material prepared by the peroxidase-promoted catechol and fiber cross-linking modification treatment, after incubation for 120 minutes, the removal rate of sodium nitrite was 36.7%;

[0019] (b) For the PMP pulp of eucalyptus mechanical pulp, the antibacterial packaging material prepared by the peroxidase-promoted catechol and fiber cross-linking modification treatment, after incubation for 120 minutes, the removal rate of sodium nitrite was 43.3%;

[0020] (c) for the PMP pulp of eucalyptus mechanical pulp, the antibacterial packaging material prepared by the peroxidase-promoted catechol and fiber cross-linking modification treatment has a reflectivity of no more than 30% in the entire visible region of 400nm-800nm;

[0021] (d) For the MP pulp of eucalyptus mechanical pulp, the C1 component in the C1 sXPS of the fiber of the antibacterial packaging material prepared by the peroxidase-promoted catechol and fiber cross-linking modification treatment is 52.73%;

[0022] (e) For the PMP pulp of eucalyptus mechanical pulp, the antibacterial packaging material prepared by the peroxidase-promoted catechol and fiber cross-linking modification treatment has an air permeability of 41.25 μm·Pa-1·s-1;

[0023] The PMP pulp described in the above conditions (b), (c) and (e) refers to PMP pulp that has been treated with biological enzymes, chelated and bleached with hydrogen peroxide.

[0024] The present application also provides a method for preparing the antibacterial packaging material as described in any one of the schemes, the method comprising the following steps:

[0025] (1) Selecting MP pulp or PMP pulp of eucalyptus mechanical pulp, wherein the acid-soluble lignin content of MP pulp and PMP pulp is 4.1% and 3.0% respectively, and the Klason lignin content is 23.8% and 18.7% respectively;

[0026] (2) Enzyme-catalyzed fiber surface cross-linking, the specific process includes:

[0027] Guaiacol, catechol and gallic acid are added into the MP pulp and PMP pulp of eucalyptus mechanical pulp at the amount of 0.05g / g absolute dry pulp, and 0.02g / g absolute dry pulp of peroxidase extracted from natural plants and 0.3g / L H2O2 are added, and the mixture is stirred at room temperature for 24h; after the reaction is completed, the peroxidase is inactivated by boiling, and the unreacted residue is eluted with acetone and washed with deionized water to obtain eucalyptus mechanical pulp MP pulp cross-linked with polyguaiacol, polycatechol and polygallic acid, which are recorded as GL-MP, CL-MP and GA-MP respectively; and eucalyptus mechanical pulp PMP pulp cross-linked with polyguaiacol, polycatechol and polygallic acid are obtained, which are recorded as GL-PMP, CL-PMP and GA-PMP respectively;

[0028] (3) Sheet making: The slurry obtained in step (2) was heated to 60 ± 1.5 g / m 2 The quantitative sheets are copied and then placed in a constant temperature and humidity chamber for 24 hours. The temperature of the constant temperature and humidity chamber is 23° C. and the relative humidity is 50%. The preparation is now completed.

[0029] As a further improvement to the above scheme, in step (2), the concentration of the MP pulp and PMP pulp of the eucalyptus mechanical pulp is 5%, and they are prepared using a phosphate buffer solution of 0.1 mol / L and pH 5.0.

[0030] As a further improvement to the above scheme, the biological enzyme is peroxidase, which is extracted from natural plants, and the extraction method includes:

[0031] Wash with deionized water and drain; weigh 100 leaves of Eryngium scabra, cut the leaves to less than 2 cm, mix with 150 mL of phosphate buffer solution with a concentration of 0.01 mol / L and pH 5, put into a plant wall breaking machine for high-speed wall breaking for 1 min to obtain a homogenate, then filter with 8 layers of absorbent cotton gauze, and then centrifuge for 10 min to remove the filter residue to obtain a clear liquid, which is used as the initial liquid for subsequent separation and extraction, recorded as water extract; slowly drip the water extract into a certain volume of acetone, stir while dripping, stand at 4°C for 15 min, centrifuge for 10 min to remove the supernatant, obtain a precipitate, dissolve the precipitate with phosphate buffer, make the volume to 100 mL, centrifuge again to remove insoluble matter, and obtain a crude enzyme solution;

[0032] Purification of crude peroxidase solution

[0033] The crude enzyme solution obtained by acetone extraction is pumped into an ion exchange chromatography column to remove pigments and impurities, specifically including:

[0034] (1) Ion exchanger pretreatment: DEAE cellulose-DE52 was soaked in deionized water for 3 h, soaked in 0.5 mol / L NaOH solution for 30 min, then washed with deionized water until neutral, and then soaked in 0.5 mol / L HCl solution for 30 min and washed again until neutral;

[0035] (2) Column loading: The pretreated DEAE cellulose-DE52 was loaded into the chromatography column, and the chromatography column was fully equilibrated with 0.01 mol / L phosphate buffer solution at pH 5;

[0036] (3) Sample loading: 7 mL of crude enzyme solution was added and balanced with 15 mL of phosphate buffer solution;

[0037] (4) Elution and collection: During elution, 2 mol / L NaCl solution and phosphate buffer solution were used for gradient mixed elution. One tube of sample was collected every 5 minutes. The elution time was 2 hours, and a total of 24 tubes of samples were collected; the peroxidase activity of each tube of sample was detected;

[0038] (5) Regeneration of the exchanger: Use 1 mol / L HCl and 1 mol / L NaOH for transformation regeneration. If the regenerated ion exchanger is not used for a long time, store it at 4°C to prevent microbial growth;

[0039] Desalting and freeze drying of peroxidase

[0040] The enzyme solution after ion exchange chromatography is desalted in an ultrafiltration centrifuge tube, the enzyme solution is placed in an ultrafiltration centrifuge tube, centrifuged at 5000 rpm for 10 minutes, the enzyme trapped in the centrifuge tube is dissolved in deionized water, centrifuged again, and the above operation is repeated several times until no Cl- is detected in the centrifuge liquid passing through the filter membrane; finally, the trapped enzyme is dissolved in a phosphate buffer, and freeze-dried into powder in a vacuum freeze dryer to obtain peroxidase;

[0041] Wherein, in step A, the centrifugation conditions are 4°C, 10000rpm; in step B, the diameter of the chromatography column is 1.6cm and the length is 30cm.

[0042] In addition, the present application also claims protection for the use of an antibacterial packaging material as described in any of the previous technical solutions in food packaging or preservation or storage, and / or antibacterial and antioxidant dressings / patches / sheets.

[0043] Beneficial technical effects

[0044] The present invention successfully cross-links phenolic substances to eucalyptus mechanical pulp, a main component of seafood packaging materials, with the help of biological enzymes, so that the cross-linked eucalyptus mechanical pulp obtains unexpected antibacterial and antioxidant properties, and then the paper or packaging material prepared from the eucalyptus mechanical pulp obtains the functional properties of degrading nitrite, resisting Vibrio and antioxidant. As a packaging material for seafood, it has certain practical value in preserving and improving quality, inhibiting the growth of harmful microorganisms and anti-oxidation, and is a completely innovative solution in the field of seafood packaging materials.

[0045] The biological enzyme used in this application is extracted from natural plant leaves, and an extraction method is given. The extracted natural peroxidase is applied to pulp to promote the cross-linking of phenolic substances and fibers, realizing the innovative and creative application of natural biological enzymes instead of artificial synthetic biological enzymes in paper-based packaging materials. This not only realizes the resource application of palm plants, but also provides a reference and reference for the more environmentally friendly and pollution-free production of paper-based pulp. At the same time, the prepared packaging material has excellent antibacterial, antioxidant and anti-corrosion effects, and good air permeability, which provides excellent fresh-keeping and antibacterial materials for the widespread use of paper-based materials in food, such as seafood, cooked food, etc. packaging and storage, and also provides prospects and space for expanding the extensive resource application of paper-based materials.

[0046] The antibacterial packaging material provided in the present application has a simple preparation method compared to the antibacterial materials prepared by other methods in the prior art, and the biological enzymes used are extracted from natural plant leaves, which reduces the use of chemical reaction reagents in the packaging material, making the packaging material more environmentally friendly and healthy, and improving the safety of use of the packaged and stored food, as well as the greening of the preparation process.

[0047] This application verifies the cross-linking effect of different types of phenols on MP pulp and PMP pulp of eucalyptus mechanical pulp under the promotion of peroxidase, and conducts a variety of tests on the cross-linked fibers, including a series of data statistics and characterizations such as antibacterial, antioxidant, optical properties, strength properties, thermal stability, air permeability, etc., and obtains better cross-linking treatment modes and methods, which creates a technical foundation and theoretical basis for further improving the efficient and high-quality application of antibacterial and anti-oxidant packaging materials and meeting the application needs in related fields, and provides technical support for the expansion research of this method and the market application of products. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 :Photos of enzyme-modified mechanical pulp sheets and statistical analysis of their optical properties;

[0049] Figure 2 : SEM image of enzymatically modified mechanical pulp (magnified 500 times);

[0050] Figure 3 : FT-IR images of enzyme-modified mechanical pulp, where: (a) unbleached pulp; (b) bleached pulp;

[0051] Figure 4 : XPS low-resolution spectrum of enzyme-modified mechanical pulp;

[0052] Figure 5 : C1 s peak spectrum of enzymatically modified mechanical pulp;

[0053] Figure 6 : Statistical diagram of the effect of enzymatic modification on the physical properties of mechanical pulp, including: (a) tensile index; (b) tear index; (c) burst index; (d) air permeability;

[0054] Figure 7 :Analysis chart of thermal stability of enzyme-modified mechanical pulp (a) unbleached pulp; (b) bleached pulp

[0055] Figure 8 :Statistical graph of the inhibitory effect of enzymatically modified mechanical pulp sheets on V.fischeri;

[0056] Fig. 9 : Analysis of the removal effect of enzymatically modified mechanical pulp sheets on sodium nitrite, including: (a) MP series; (b) PMP series;

[0057] Fig.10 : Analysis of the antioxidant properties of enzyme-modified mechanical pulp sheets. DETAILED DESCRIPTION

[0058] The technical solutions of the specific embodiments of the present invention will be clearly and completely described below in combination with various specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The experimental methods described in the following embodiments are all conventional methods unless otherwise specified; the reagents and materials, unless otherwise specified, can be obtained through ordinary commercial channels.

[0059] Description of experimental reagents

[0060] The guaiacol, catechol, gallic acid, lignin, 2,2-azino-bis(3-ethyl-benzothiazole-6-sulfonic acid) diammonium salt (ABTS), potassium persulfate (K2S2O4) and sodium nitrite (NaNO2) used in the present invention are all analytically pure and purchased from Shanghai MacLean Biotechnology Co., Ltd.; the nitrite detection kit was purchased from Guangdong Huankai Microbiology Co., Ltd.; and the Vibrio fischeri kit was purchased from Guangzhou Bolu Teng Biotechnology Co., Ltd.

[0061] The specific technical solution is:

[0062] An antibacterial packaging material, characterized in that the antibacterial packaging material satisfies at least one of the following conditions:

[0063] (4) The water contact angle of the antimicrobial packaging material is between 27.82±1.58° and 48.79±0.62°;

[0064] (5) The inhibition rate of the antibacterial packaging material on Vibrio fischeri after incubation for 30 minutes is greater than or equal to 21.2%;

[0065] (6) The inhibition rate of the antibacterial packaging material on Vibrio fischeri after incubation for 60 minutes is greater than or equal to 41.6%.

[0066] As a further improvement to the above scheme, the antibacterial packaging material is obtained by treating eucalyptus mechanical pulp with bio-enzyme-promoted phenols and fiber cross-linking modification, and the eucalyptus mechanical pulp is selected from MP pulp or PMP pulp.

[0067] As a further improvement to the above solution, the antibacterial packaging material satisfies at least one of the following conditions:

[0068] (1) When the eucalyptus mechanical pulp is MP pulp, the antibacterial packaging material prepared by subjecting it to biological enzyme-promoted phenolic and fiber cross-linking modification treatment has an inhibition rate of Vibrio fischeri greater than or equal to 18.0% after incubation for 30 minutes;

[0069] (2) When the eucalyptus mechanical pulp is PMP pulp, the antibacterial packaging material prepared by subjecting it to bio-enzyme-promoted phenolic and fiber cross-linking modification treatment has an inhibition rate of Vibrio fischeri greater than or equal to 26.4% after incubation for 60 minutes, wherein the PMP pulp of the eucalyptus mechanical pulp is PMP pulp that has been treated with bio-enzyme, chelate, and hydrogen peroxide bleaching in sequence.

[0070] As a further improvement to the above solution, the biological enzyme is specifically peroxidase extracted from natural palm plants.

[0071] As a further improvement to the above scheme, the phenols are specifically guaiacol, catechol, and gallic acid.

[0072] As a further improvement to the above scheme, when the phenol is selected as catechol, the biological enzyme is selected as peroxidase extracted from natural palm plants, and the antibacterial packaging material meets at least one of the following conditions:

[0073] (a) For the MP pulp of eucalyptus mechanical pulp, the antibacterial packaging material prepared by the peroxidase-promoted catechol and fiber cross-linking modification treatment, after incubation for 120 minutes, the removal rate of sodium nitrite was 36.7%;

[0074] (b) For the PMP pulp of eucalyptus mechanical pulp, the antibacterial packaging material prepared by the peroxidase-promoted catechol and fiber cross-linking modification treatment, after incubation for 120 minutes, the removal rate of sodium nitrite was 43.3%;

[0075] (c) for the PMP pulp of eucalyptus mechanical pulp, the antibacterial packaging material prepared by the peroxidase-promoted catechol and fiber cross-linking modification treatment has a reflectivity of no more than 30% in the entire visible region of 400nm-800nm;

[0076] (d) For the MP pulp of eucalyptus mechanical pulp, the C1 component in the C1 sXPS of the fiber of the antibacterial packaging material prepared by the peroxidase-promoted catechol and fiber cross-linking modification treatment is 52.73%;

[0077] (e) For the PMP pulp of eucalyptus mechanical pulp, the antibacterial packaging material prepared by the peroxidase-promoted catechol and fiber cross-linking modification treatment has an air permeability of 41.25 μm·Pa-1·s-1;

[0078] The PMP pulp described in the above conditions (b), (c) and (e) refers to PMP pulp that has been treated with biological enzymes, chelated and bleached with hydrogen peroxide.

[0079] The present application also provides a method for preparing the antibacterial packaging material as described in any one of the schemes, the method comprising the following steps:

[0080] (4) Selecting MP pulp or PMP pulp of eucalyptus mechanical pulp, wherein the acid-soluble lignin content of MP pulp and PMP pulp is 4.1% and 3.0% respectively, and the Klason lignin content is 23.8% and 18.7% respectively;

[0081] (5) Bio-enzyme catalyzes fiber surface cross-linking. The specific process includes:

[0082] Guaiacol, catechol and gallic acid are added into the MP pulp and PMP pulp of eucalyptus mechanical pulp at the amount of 0.05g / g absolute dry pulp, and 0.02g / g absolute dry pulp of peroxidase extracted from natural plants and 0.3g / L H2O2 are added, and the mixture is stirred at room temperature for 24h; after the reaction is completed, the peroxidase is inactivated by boiling, and the unreacted residue is eluted with acetone and washed with deionized water to obtain eucalyptus mechanical pulp MP pulp cross-linked with polyguaiacol, polycatechol and polygallic acid, which are recorded as GL-MP, CL-MP and GA-MP respectively; and eucalyptus mechanical pulp PMP pulp cross-linked with polyguaiacol, polycatechol and polygallic acid are obtained, which are recorded as GL-PMP, CL-PMP and GA-PMP respectively;

[0083] (6) Sheet making: The slurry obtained in step (2) was heated to 60 ± 1.5 g / m 2 The quantitative sheets are copied and then placed in a constant temperature and humidity chamber for 24 hours. The temperature of the constant temperature and humidity chamber is 23° C. and the relative humidity is 50%. The preparation is now completed.

[0084] As a further improvement to the above scheme, in step (2), the concentration of the MP pulp and PMP pulp of the eucalyptus mechanical pulp is 5%, and they are prepared using a phosphate buffer solution of 0.1 mol / L and pH 5.0.

[0085] As a further improvement to the above scheme, the biological enzyme is peroxidase, which is extracted from natural plants, and the extraction method includes:

[0086] Wash with deionized water and drain; weigh 100 leaves of Eryngium scabra, cut the leaves to less than 2 cm, mix with 150 mL of phosphate buffer solution with a concentration of 0.01 mol / L and pH 5, put into a plant wall breaking machine for high-speed wall breaking for 1 min to obtain a homogenate, then filter with 8 layers of absorbent cotton gauze, and then centrifuge for 10 min to remove the filter residue to obtain a clear liquid, which is used as the initial liquid for subsequent separation and extraction, recorded as water extract; slowly drip the water extract into a certain volume of acetone, stir while dripping, stand at 4°C for 15 min, centrifuge for 10 min to remove the supernatant, obtain a precipitate, dissolve the precipitate with phosphate buffer, make the volume to 100 mL, centrifuge again to remove insoluble matter, and obtain a crude enzyme solution;

[0087] Purification of crude peroxidase solution

[0088] The crude enzyme solution obtained by acetone extraction is pumped into an ion exchange chromatography column to remove pigments and impurities, specifically including:

[0089] (1) Ion exchanger pretreatment: DEAE cellulose-DE52 was soaked in deionized water for 3 h, soaked in 0.5 mol / L NaOH solution for 30 min, then washed with deionized water until neutral, and then soaked in 0.5 mol / L HCl solution for 30 min and washed again until neutral;

[0090] (2) Column loading: The pretreated DEAE cellulose-DE52 was loaded into the chromatography column, and the chromatography column was fully equilibrated with 0.01 mol / L phosphate buffer solution at pH 5;

[0091] (3) Sample loading: 7 mL of crude enzyme solution was added and balanced with 15 mL of phosphate buffer solution;

[0092] (4) Elution and collection: During elution, 2 mol / L NaCl solution and phosphate buffer solution were used for gradient mixed elution. One tube of sample was collected every 5 minutes. The elution time was 2 hours, and a total of 24 tubes of samples were collected; the peroxidase activity of each tube of sample was detected;

[0093] (5) Regeneration of the exchanger: Use 1 mol / L HCl and 1 mol / L NaOH for transformation regeneration. If the regenerated ion exchanger is not used for a long time, store it at 4°C to prevent microbial growth;

[0094] Desalting and freeze drying of peroxidase

[0095] The enzyme solution after ion exchange chromatography is desalted in an ultrafiltration centrifuge tube, the enzyme solution is placed in an ultrafiltration centrifuge tube, centrifuged at 5000 rpm for 10 minutes, the enzyme trapped in the centrifuge tube is dissolved in deionized water, centrifuged again, and the above operation is repeated several times until no Cl- is detected in the centrifuge liquid passing through the filter membrane; finally, the trapped enzyme is dissolved in a phosphate buffer, and freeze-dried into powder in a vacuum freeze dryer to obtain peroxidase;

[0096] Wherein, in step A, the centrifugation conditions are 4°C, 10000rpm; in step B, the diameter of the chromatography column is 1.6cm and the length is 30cm.

[0097] In addition, the present application also claims to protect the use of an antibacterial packaging material as described in any of the previous technical solutions in food packaging, preservation or storage. Here, the food can be fresh seafood, frozen seafood, various cooked food, raw food, dairy products, and any other food that needs to be packaged. Of course, the application scope of the packaging material of the present application can also be expanded to other materials that require antibacterial and anti-oxidation, such as anti-oxidation and antibacterial materials for treating wounds, anti-inflammatory plasters for treating skin closures, redness and swelling, and skin compresses, etc.

[0098] The pulp raw materials used in the present invention are eucalyptus mechanical pulp (MP) that has not been delignified and bleached pulp (PMP) that has been delignified and bleached by XQP, wherein:

[0099] The above X represents: X-stage treatment (biological enzyme treatment), the treatment conditions are: pulp concentration 10%, pH 5.0, temperature 60°C, enzyme dosage 1.5g / kg absolute dry pulp, treatment time 4h, H2O2 addition amount 0.3g / L;

[0100] The conditions of the Q stage treatment (chelating treatment) are as follows: pulp concentration 10%, temperature 60°C, 0.5% EDTA, and treatment time 1 h.

[0101] The conditions of the P stage treatment (hydrogen peroxide bleaching treatment) are: pulp concentration 10%, H2O24%, NaOH2%, MgSO40.5%, temperature 80°C, and time 2h.

[0102] The acid-soluble lignin contents of MP and PMP were 4.1% and 3.0%, respectively, and the Klason lignin contents were 23.8% and 18.7%, respectively.

[0103] Among them, the biological enzyme used in the X-stage treatment is peroxidase extracted from natural plants. The specific extraction process is as follows:

[0104] Obtaining crude peroxidase solution

[0105] The natural plant is collected to extract peroxidase, and the process includes:

[0106] Wash with deionized water and drain; weigh 100g of leaves or fruits, cut the leaves to less than 2cm, mix with 150mL of phosphate buffer solution with a concentration of 0.01mol / L and pH 5, put into a plant wall breaking machine for high-speed wall breaking for 1min to obtain a homogenate, then filter with 8 layers of absorbent cotton gauze, and then centrifuge for 10min to remove the filter residue to obtain a clear liquid, which is used as the initial liquid for subsequent separation and extraction, recorded as water extract; slowly drip the water extract into a certain volume of acetone, stirring while dripping, let it stand at 4℃ for 15min, centrifuge for 10min to remove the supernatant, obtain a precipitate, dissolve the precipitate with phosphate buffer, make the volume to 100mL, centrifuge again to remove insoluble matter, and obtain a crude enzyme solution;

[0107] Purification of crude peroxidase solution

[0108] The crude enzyme solution obtained by acetone extraction is pumped into an ion exchange chromatography column to remove pigments and impurities, specifically including:

[0109] (1) Ion exchanger pretreatment: DEAE cellulose-DE52 was soaked in deionized water for 3 h, soaked in 0.5 mol / L NaOH solution for 30 min, then washed with deionized water until neutral, and then soaked in 0.5 mol / L HCl solution for 30 min and washed again until neutral;

[0110] (2) Column loading: The pretreated DEAE cellulose-DE52 was loaded into the chromatography column, and the chromatography column was fully equilibrated with 0.01 mol / L phosphate buffer solution at pH 5;

[0111] (3) Sample loading: 7 mL of crude enzyme solution was added and balanced with 15 mL of phosphate buffer solution;

[0112] (4) Elution and collection: During elution, 2 mol / L NaCl solution and phosphate buffer solution were used for gradient mixed elution. One tube of sample was collected every 5 minutes. The elution time was 2 hours, and a total of 24 tubes of samples were collected; the peroxidase activity of each tube of sample was detected;

[0113] (5) Regeneration of the exchanger: Use 1 mol / L HCl and 1 mol / L NaOH for transformation regeneration. If the regenerated ion exchanger is not used for a long time, store it at 4°C to prevent microbial growth;

[0114] Desalting and freeze drying of peroxidase

[0115] The enzyme solution after ion exchange chromatography is desalted with an ultrafiltration centrifuge tube, the enzyme solution is placed in the ultrafiltration centrifuge tube, centrifuged at 5000rpm for 10 minutes, the enzyme trapped in the centrifuge tube is dissolved with deionized water, centrifuged again, and the above operation is repeated many times until Cl- is not detected in the centrifuge liquid passing through the filter membrane; finally, the trapped enzyme is dissolved in phosphate buffer, and freeze-dried into powder with a vacuum freeze dryer to obtain peroxidase.

[0116] Wherein, in step A, the centrifugation conditions are 4°C, 10000rpm; in step B, the diameter of the chromatography column is 1.6cm and the length is 30cm.

[0117] After extraction, the obtained natural catalase activity was measured to be 35.64±4.77U / mL, the best reaction pH was pH 5.0, and the temperature was 60°C.

[0118] Fiber surface cross-linking catalyzed by bio-enzyme

[0119] Guaiacol, catechol and gallic acid were added to MP and XQP treated PMP slurry (5% slurry concentration, prepared with 0.1 mol / L, pH 5.0 phosphate buffer) at 0.05 g / g absolute dry pulp, PRLP at 0.02 g / g absolute dry pulp and H2O2 at 0.3 g / L, and stirred at room temperature for 24 hours. After the reaction was completed, the enzyme was inactivated by boiling, the unreacted residue was eluted with acetone and washed with deionized water, and MP cross-linked with polyguaiacol (GL-MP), polycatechol (CL-MP) and polygallic acid (GA-MP) and PMP cross-linked with polyguaiacol (GL-XQP), catechol (CL-PMP) and polygallic acid (GA-PMP) were obtained, and MP and PMP without cross-linking modification were used as controls.

[0120] Copy

[0121] Using enzymatic cross-linked eucalyptus mechanical pulp and undelignified eucalyptus mechanical pulp as raw materials, the ratio of 60±1.5g / m 2 The quantitative copying method is as follows:

[0122] The pulp was placed in a deflaker and deflaked for 2000 revolutions. The paper was made using a Kaiser automatic papermaking system (RK3AKWT, Austria RK3A). The basis weight of the paper was 60±1.5 g / m 2 , and then placed in a constant temperature and humidity chamber (temperature 23°C, relative humidity 50%) for 24 hours for measuring paper properties.

[0123] Optical properties and microscopic feature analysis

[0124] Optical properties

[0125] Under standard light source D65, the color of the modified paper was measured with a whiteness meter (Elrepho070, Lorentzen & Wettre, Sweden). The color of the sample was described by the CIEL*a*b* color system, where L*, a* and b* are the coordinates of the color in the color space, L* represents brightness, 0 is absolute black, 100 is white, a* is the change from green (negative value) to red (positive value), and b* is the change from blue (negative value) to yellow (positive value). Chroma (C*) represents color saturation, and its calculation formula is:

[0126]

[0127] Microscopic features

[0128] The surface of the enzyme-modified mechanical pulp was observed using a field emission scanning electron microscope (FE-SEM). The paper was attached to a sample stage with conductive glue attached in advance, and then plated with gold (platinum) and observed using a FE-SEM (Merlin, Zeiss, Germany).

[0129] Spectral analysis

[0130] Ultraviolet-Visible Diffuse Reflectance Spectroscopy (UV-VisDRS)

[0131] UV-Vis DRS mainly uses the reflection of light on the surface of a material to obtain information about the composition and structure of the material. The paper is cut into 2 cm × 4 cm pieces and placed in a sample slot. The reflectivity of the paper is tested using a UV-visible spectrophotometer (UV-2600i, Shimadzu).

[0132] Fourier transform infrared spectroscopy (FT-IR)

[0133] The surface functional groups of the modified paper were tested by FT-IR. The samples were cut into pieces and ground evenly with KBr powder, and then pressed into sheets. The transmittance in the wave number range of 4000 to 400 cm-1 was measured by Fourier transform infrared spectrometer (TENSOR37, Bruker, Germany).

[0134] X-ray Photoelectron Spectroscopy (XPS)

[0135] XPS was used to test the changes in the surface elements of the modified paper. The XPS test method is as follows:

[0136] Accurately weigh 2.0g of pulp with an absolute dry mass, wrap it with pre-extracted filter paper, and extract it with acetone in a Soxhlet extractor for 6 hours to remove the extract. Then wash it with deionized water until it is neutral, flatten it on a glass plate to make a pulp sheet, and air-dry it at room temperature. Use an X-ray photoelectron spectrometer for measurement and analysis. Use the following formula to estimate the content of lignin on the fiber surface.

[0137]

[0138] Among them, O / C 碳水化合物 =0.83, O / C 木质素 =0.33.

[0139] Physical performance analysis

[0140] Tensile strength determination

[0141] The tensile index of the paper was measured in a tensile strength instrument (L&WCE062, Lorentzen & Wettre, Sweden). The sample width was 15 mm and the length was 150 mm. The maximum tensile strength, i.e. the maximum tension that the paper can withstand, was measured 3 times for each set of conditions and the average value was taken. The tensile index was calculated by dividing the tensile strength by the paper basis weight.

[0142] Bursting strength determination

[0143] The maximum bursting strength of the paper (bursting index is the ratio of bursting strength to paper basis weight) is measured in a bursting strength tester (L&WCE180, Lorentzen & Wettre, Sweden), that is, the maximum pressure that paper can withstand per unit area. Place the test sample on the top of the instrument diaphragm, press the "Start" button to test, and record the data. Each set of conditions is measured 3 times and the average value is taken.

[0144] Tear strength determination

[0145] The tear strength of the paper was tested in a tear tester (L&W009, Lorentzen & Wettre, Sweden) (the tear index is the ratio of the tear strength to the basis weight of the paper sheet). The paper sample size is 63mm×50mm, fixed on the fixture, press the "CLAMP" key to cut the paper, press the "PEND" key to test, record the data, measure 3 times for each set of conditions, and take the average value.

[0146] The air permeability of paper was measured using an air permeability meter (L&W166, Lorentzen & Wettre, Sweden). The paper sample was placed on the air permeability meter, and the instrument started the test after clamping. The test results were read after the test was completed. Each group of conditions was tested 3 times and the average value was taken.

[0147] The thermal stability of the modified paper was tested using a thermogravimetric analyzer (TG209F3, Netzsch, Germany). The sample was about 5 mg, the temperature test range was 50-600°C, and the heating rate was 20°C / min.

[0148] The water contact angle of the modified paper surface was measured using a liquid surface tension meter (OCA40, Dataphysics, Germany).

[0149] 80 μL of water was carefully dropped onto the sample surface using the sessile drop method. After the system took a photo, the SCA21-22 software module was used to evaluate the droplet profile on the sample surface and obtain the water contact angle measurement value. Each set of conditions was tested 3 times and the average value was taken.

[0150] Biological activity test

[0151] Nitrite degradation experiment

[0152] The degradation effect of nitrite on phenol-modified paper was determined using a nitrite detection kit.

[0153] 0.1~0.5mg / L sodium nitrite solution, take 15mL sodium nitrite solution in a colorimetric bottle, add reagent I, let stand for 5min after fully dissolving, then add reagent II, let stand for 10min after fully mixing, and use a UV-visible spectrophotometer to measure the absorbance at 540nm. With the concentration of sodium nitrite as the horizontal coordinate (x) and the absorbance as the vertical coordinate (y), the standard curve equation is obtained: y=0.862x+0.0062, R2=0.9998, n=6.

[0154] When testing the sample, cut the paper into pieces of about 1.5cm×1.5cm (weight 15mg), add them to a 0.3mg / L (q0) sodium nitrite solution, incubate for 30min, 60min, 90min and 120min at 25℃, 50℃ and 80℃, respectively, then add the detection reagent using the above method, measure the absorbance at 540nm, and calculate the residual amount of sodium nitrite (qt) using the standard curve equation. Use the following formula to calculate the degradation rate D (%) of sodium nitrite.

[0155]

[0156] Vibrio fischeri inhibition test

[0157] The inhibitory performance of paper samples on luminous bacteria was tested using a Vibrio fischeri (V.fischeri) test kit

[145] . 0.1 mL of NaCl solution (21 wt%) and 0.5 mL of V.fischeri bacterial solution were added to the test tube, followed by 1 mg of paper sample, and incubated at 25 °C for 30 and 60 min, respectively. The luminescence intensity of V.fischeri (S0 and St) before and after incubation was tested on a portable water quality toxicity rapid detector (BLTLux-T010, Bo Lu Teng, China). Ultrapure water was used as a blank control (C0 and Ct), and the inhibition rate (IPvf) of the modified paper on V.fischeri was calculated using formula 4-3.

[0158]

[0159] Antioxidant test

[0160] ABTS is easily oxidized by potassium persulfate to green ABTS+·. The presence of antioxidants will inhibit the production of ABTS+· or scaveng it. The free radical scavenging ability of the sample can be calculated by measuring the absorbance of ABTS at 734nm.

[0161] The preparation method of ABTS working stock solution is as follows:

[0162] Mix 1 mL ABTS solution (7.4 mmol / L) and 1 mL K2S2O4 (2.6 mmol / L) and shake well, and store at room temperature away from light for 12 hours. During the test, dilute the working stock solution with anhydrous ethanol to an absorbance of 0.70±0.02 at 734 nm as the working solution. During the experiment, add 1 mL ABTS working solution and 2 mg paper sample to the test tube, incubate for 15 and 30 minutes respectively under light-proof conditions (25°C), measure the absorbance At at 734 nm at the end, and use anhydrous ethanol as the blank control A0. Calculate the free radical scavenging rate (RROS) according to the formula below.

[0163]

[0164] Optical properties and microscopic characteristics of enzymatically cross-linked modified fibers

[0165] After cross-linking guaiacol (GL), catechol (CL) and gallic acid (GA) on the surface of eucalyptus mechanical pulp, the most prominent change in appearance is the darkening of the color ( Figure 1 In a), this is the result of peroxidase oxidizing phenolic substrates to generate quinone structure polymers. Especially for mechanical pulp (PMP) treated with XQP, the color contrast is very obvious.

[0166] CL-PMP is the darkest in color, black; GL-PMP is the second darkest, pink; GA-PMP is also darker in color (bluish gray), but not as obvious as the first two. Mechanical pulp without XQP treatment - MP pulp is obviously brown, GL-MP and GA-MP obtained by enzymatic modification are not much different in color from the original MP, and CL-MP is dark gray. The apparent color is an important element of packaging materials. The use of peroxidase to catalyze phenolic substances to generate colored substances on the surface of mechanical pulp in situ is more environmentally friendly and safer than adding chemical synthetic dyes to the pulp.

[0167] The diffuse reflectance spectrum of paper is Figure 1 As shown in b, the reflectivity of CL-PMP in the entire visible region (400nm-800nm) does not exceed 30%, showing strong absorption of the entire visible light band, so it appears black. CL-MP also absorbs visible light in the range of 400nm-800nm, and its reflectivity (>50%) is higher than that of CL-PMP. Like the latter, its reflectivity increases with increasing wavelength, so it is described as dark gray. GL-PMP and GA-PMP have obvious peaks (shoulders) at 470nm and 540nm, respectively, corresponding to red and blue features. The reflectance spectra of GL-MP and GA-MP are close to those of the MP control group, so the apparent color is not much different.

[0168] The L*a*b* values ​​of the film obtained by color difference analysis are as follows Figure 1As shown in c, L* represents lightness and darkness (black and white), a* represents red and green, b* represents yellow and blue, and c* represents the degree of color saturation or purity. PMP has the largest L* value and is the whitest. The L* values ​​of pulps modified by enzymatic phenols all decreased. GL-MP, CL-MP and GA-MP decreased by 5.3%, 19.2% and 9.4% respectively relative to MP, and GL-PMP, CL-PMP and GA-PMP decreased by 21.4%, 38.7% and 14.3% respectively relative to PMP. CL-PMP has the smallest L* and c* values ​​and is the most black. From Figure 1 As can be seen from figure d, the red feature of GL-PMP is the most obvious, and the a* value of GL-MP is 87% higher than that of the MP control sample; the color difference between GA-MP and GA-PMP relative to their respective reference samples is very small, indicating that GA polymerization and cross-linking do not produce bright red-green or yellow-blue, which is consistent with the diffuse reflectance spectrum results.

[0169] Spectral and color difference analysis confirmed that there were color differences in the polymers produced by peroxidase and different phenolic reactants. The chromogenic group may be formed by the polymerization of monomers or the result of the polymerization reaction of monomers with the aromatic ring of lignin. The polymer can be further oxidized into a dark quinone structure under the action of the enzyme. Since catechol contains two adjacent phenolic hydroxyl groups, the orthoquinone formed is generally red or orange. After the polymerization of guaiacol, the monomer only contains a semiquinone structure, so the color is lighter. Gallic acid also forms an orthoquinone structure because the three sites of the aromatic ring C3, C4, and C5 are all substituted by hydroxyl groups, but the color change is not obvious.

[0170] The mechanical pulp fibers before and after enzymatic phenolic cross-linking modification were observed using SEM. Figure 2 As shown in the figure, the surface of MP fiber becomes rough after cross-linking, which is speculated to be due to the deposition of enzyme-catalyzed phenolic substrates on the fiber surface after polymerization, increasing the roughness of MP. PMP fiber surface is damaged due to biological and chemical reactions and is rougher than MP, but the fiber surface becomes smooth and flat after GL, CL and GA cross-linking modification reaction, which may be due to the polymer filling the surface depression of PMP fiber caused by bleaching, making the fiber more uniform. From the SEM results, it can be seen that the connection between pulp fibers after cross-linking modification is tighter, and the polymer produces adhesion between layers, which plays a role similar to "adhesive", indicating that this adhesion improves the mechanical strength of paper.

[0171] Surface chemical analysis of enzymatically cross-linked fibers

[0172] FT-IR spectral characteristics

[0173] The FT-IR spectra of pulp before and after modification are shown in Figure 2. Figure 3 As shown, 3427cm -1The broad absorption peak at 2900 cm-1 is the OH stretching vibration. -1 The broad absorption peaks at 1730 cm-1 are due to the antisymmetric and symmetric stretching vibrations of methyl and methylene groups. -1 The absorption peak at 1633 cm is the C=O stretching vibration of the non-conjugated ketone carbonyl or ester bond. -1 The broad absorption peak at 1507 cm is the OH bending vibration of cellulose bound water and the C=O stretching vibration of conjugated carbonyl. -1 The absorption peak at 1370 cm is the stretching vibration of the benzene ring skeleton. -1 The absorption peak at 1267 cm is the symmetrical vibration of methyl group. -1 The absorption peak at 1064 cm is the CO stretching vibration of phenolic hydroxyl group. -1 The broad absorption peak at 896 cm is the CO stretching vibration of the alcohol hydroxyl group, the COC stretching vibration of the ether, and the CH in-plane bending vibration of the benzene ring. -1 The absorption peak at 613 cm is the in-plane bending vibration of the CH ring. -1 The broad absorption peak at is the bending vibration of hydroxyl OH. After enzymatic cross-linking modification of GL, CL and GA, the non-conjugated carbonyl C=O or stretching vibration signal weakened, and the conjugated carbonyl C=O stretching vibration signal strengthened. This is because the phenolic polymer formed by enzyme catalysis is further converted into a quinone conjugated structure, which also shows that the three phenols are successfully cross-linked to the pulp.

[0174] XPS spectrum characteristics

[0175] The modification of pulp by peroxidase mainly occurs on the fiber surface. Due to the cross-linking of free radicals, phenolic substances are polymerized and deposited on the fiber surface or cross-linked with lignin. The present invention uses XPS to measure the O / C ratio of the mechanical pulp fiber surface before and after modification to explore this mechanism. The results are as follows: Figure 4As shown in Table 1. After modification, the O / C ratio of the fiber surface decreased, and the concentration of total non-carbohydrate aromatic substances increased. The O / C ratios of GL-MP, CL-MP and GA-MP were 0.3%, 1.4% and 1.1% lower than that of MP, respectively, and the O / C ratios of GL-PMP, CL-PMP and GA-PMP were 1.4%, 0.9% and 1.1% lower than that of PMP, respectively. Since the O / C of carbohydrates is as high as 0.83, the average O / C of eucalyptus lignin is 0.33, and the O / C of GL, CL and GA are 0.28, 0.33 and 0.71, respectively, which indicates that peroxidase catalysis leads to the polymerization and deposition of phenolic substances on the fiber surface, which may not only cover the surface of lignin or copolymerize with lignin, but also cover part of the carbohydrate surface. In addition, the total aromatic concentrations of GL-MP, CL-MP and GA-MP were 0.3%, 1.3% and 1.0% higher than those of MP, respectively, and the total aromatic concentrations of GL-PMP, CL-PMP and GA-PMP were 2.8%, 2.0% and 2.6% higher than those of PMP, respectively. This indicates that peroxidase-catalyzed modification increases the proportion of non-carbohydrates, which may slightly affect the hydrophilicity / hydrophobicity of the fiber surface and the fiber cross-linking strength, which will be demonstrated in subsequent experiments. Compared with MP, the concentration of total aromatic substances on the fiber surface increased the most after adding CL modification, while the concentration of total aromatic substances on the fiber surface increased the most after adding GL relative to PMP.

[0176] Table 1 Summary of XPS analysis of enzyme-modified mechanical pulp

[0177]

[0178] In order to further discuss the changes in the concentration of chemical components on the fiber surface, the C1 sXPS spectrum of the fiber is fitted with the following curve: Figure 5 As shown. Due to the increase in the concentration of total aromatic substances on the fiber surface, the C1 component of GL, CL and GA modified MP pulps catalyzed by peroxidase increased from 51.44% to 52.60%, 52.73% and 51.99%, respectively. Relative to PMP, the C1 component after cross-linking modification increased from 31.18% to 33.48%, 33.11% and 33.33%, respectively. The C2 component of the modified pulp was lower than that of the control sample, which may be due to the coverage of carbohydrates by phenolic polymer deposition. At the same time, the C3 and C4 components in the modified pulp also increased. These changes were due to the increase in carbonyl and carboxyl content caused by the oxidation of phenolic substances and lignin by peroxidase.

[0179] Physical properties of enzymatically cross-linked fibers

[0180] Mechanical properties

[0181] After GL, CL and GA were modified by peroxidase, the physical properties of the paper sheets were tested. Figure 6 As shown in the figure, after enzyme-catalyzed cross-linking phenols (GL, CL and GA) modification, the tensile index, tear index and burst index of both unbleached pulp (MP) and XQP bleached pulp (PMP) were improved. The improvement of tensile index was the most significant ( Figure 6 a), compared with the MP control group, GL-MP, CL-MP and GA-MP increased by 42.17%, 39.76% and 39.76% respectively; compared with the PMP control group, GL-PMP, CL-PMP and GA-PMP increased by 36.36%, 21.82% and 24.55% respectively. The improvement of tensile index by cross-linked guaiacol (GL) was more significant than that by catechol (CL) and gallic acid (GA) groups. After XQP treatment and enzymatic guaiacol cross-linking modification, the tensile index of eucalyptus MP pulp increased from 20.7N·m / g to 37.5N·m / g, and the corresponding breaking length increased from 2.1km to 3.8km. According to GB13506-2008 standard, it is between the A grade (≥42N·m / g) and B grade (≥30N·m / g) of bleached sulfite hardwood pulp (45°SR).

[0182] The tearing index ( Figure 6 As for (b), the trend of the cross-linked modified fiber performance surpassing the original fiber is consistent with the tensile index. The difference in the results of the three phenolic cross-linking is more prominent. The order of tear index from high to low is

[0183] GL-MP / PMP>CL-MP / PMP>GA-MP / PMP. Cross-linked guaiacol (GL) improves the tensile index most significantly. After eucalyptus MP pulp is treated with XQP and enzymatic guaiacol cross-linking modification, the tear index increases from 3.71mN·m2 / g to 4.62mN·m2 / g. According to GB13506-2008 standard, it exceeds the index of bleached sulfite hardwood pulp (45°SR) A grade (≥3.3mN·m2 / g), and is between unbleached sulfite hardwood pulp (45°SR) B grade (≥5.0mN·m2 / g) and C grade (≥4.0mN·m2 / g).

[0184] The improvement of the bursting index by crosslinking modification is not as significant as that of the tensile index and tear index. Compared with the MP control group, the bursting index of GL-MP, CL-MP and GA-MP increased by 3.37%, 4.46% and 4.51%, respectively. Compared with the PMP control group, the bursting index of GL-PMP, CL-PMP and GA-PMP increased by 5.07%, 5.59% and 5.47%, respectively. There was no significant difference in the results obtained by crosslinking the three monomers. The crosslinking modification increased the bursting index of eucalyptus MP to the level of unbleached sulfite hardwood pulp (45°SR) B grade (≥3.5kPa·m2 / g).

[0185] The increase in physical strength may be due to the introduction of phenolic substances through cross-linking. The newly generated polymer is deposited on the fiber surface. During sheet making, it is hot pressed to fill the gaps between the fibers, thereby strengthening the hydrogen bond connection between the fibers and making the fibers more tightly connected. This tight connection tends to reduce the air permeability of the paper and make its structure denser. Figure 6 The data in Figure d show that the air permeability of MP decreased by 9.67%, 14.22% and 12.51% after modification with GL, CL and GA, respectively; while for the PMP control group, the air permeability of GL-PMP, CL-PMP and GA-PMP decreased by 7.58%, 8.03% and 1.45%, respectively. It can be seen that after the three modifications, the air barrier properties of paper are improved. In general, CL cross-linking has a better effect on reducing air permeability. After XQP treatment and enzymatic catechol (CL) cross-linking modification, the air permeability of eucalyptus MP pulp decreased from 52.7μm·Pa-1·s-1 to 41.25μm·Pa-1·s-1. The air permeability of paper made after fiber modification is reduced, making it more suitable for use as packaging materials.

[0186] Hydrophilicity and hydrophobicity

[0187] The surface contact angles of two eucalyptus mechanical pulps, MP and PMP, before and after modification are listed in Table 2. It can be seen that, from the trend, after palm peroxidase-catalyzed phenol modification, the water contact angle of the mechanical pulp decreases and the hydrophilicity increases. The modification is arranged in the order of GA>CL>GA. Specifically, the water contact angle of MP after modification with GL, CL and GA decreases from 50.47° to 48.79°, 40.23° and 27.82°, respectively, and that of PMP decreases from 37.65° to 35.42°, 33.33° and 28.33°, respectively. Gallic acid (GA) crosslinking has the most significant effect on the hydrophilic modification of mechanical pulp, which may be due to the fact that gallic acid not only contains three phenolic hydroxyl groups, but also has a carboxyl group. Catechol has two phenolic hydroxyl groups and no carboxyl group, and its hydrophilic modification effect is significantly weaker than that of GA, but still stronger than that of guaiacol (GL) which only contains one phenolic hydroxyl group.

[0188] For packaging materials, hydrophobicity is more conducive to preventing water penetration and blocking exogenous pollutants from contaminating the contents of the package with water as the medium. Therefore, if GA polymerized cross-linked fibers are used to make packaging materials, it may have a negative impact on its function due to its strong hydrophilicity. The water contact angle of GL and CL modified papers decreased within 10°. Considering their strength properties, GL and CL cross-linked modified papers have good strength properties and little decrease in hydrophobicity, and have more potential as packaging materials. However, the introduction of hydrophilic phenolic components can also improve the flexibility of the material. In the prior art, some scholars have also added GA, parahydroxybenzoic acid (HBA), ferulic acid (FA) and catechin (CAT) and other phenolic substances to plasticize the corn protein film in order to solve the brittleness and flexibility problems of corn protein film, and obtained a highly flexible film with an elongation between 135% and 189%. In the future, hydrophilic modified mechanical pulp products can be further developed along this line of thought.

[0189] Table 2 Hydrophilicity data of enzymatically modified mechanical pulp

[0190] Paper Pattern Water contact angle (°) Paper Pattern Water contact angle (°) MP 50.47±1.65 PMP 37.65±0.46 GL-MP 48.79±0.62 GL-PMP 35.42±0.83 CL-MP 40.23±0.39 CL-PMP 33.33±1.74 GA-MP 27.82±1.58 GA-PMP 28.33±2.01

[0191] Thermal stability

[0192] The thermal stability and decomposition law of enzyme-modified mechanical pulp were studied by thermogravimetric analysis (TG). Figure 7. The first thermal weight loss stage is at 50-110℃, corresponding to a mass loss of about 10%, which is attributed to the evaporation of water absorbed on the surface of the pulp. In this stage, the water loss of the GL, CL and GA cross-linked modified pulps is more than that of the control samples before modification, which is consistent with the test results of their surface hydrophilicity in the previous article. There is only one obvious weight loss peak at 300-425℃, which includes the decomposition of aromatic polymers and the degradation of cellulose. In this temperature range, the glycosidic bonds, COC bonds, and CC bonds in the cellulose structure begin to break, producing some low-molecular-weight volatile products, causing the weight loss of the main structure of the cellulose molecule. 400-600℃ is the aromatic ring of the cellulose residue to form a graphite structure. The weight loss rates of MP, GL-MP, CL-MP and GA-MP are the largest at 373℃, 375℃, 373℃ and 376℃, respectively. At 600℃, the graphite structure of the GL-MP, CL-MP and GA-MP pulps modified by phenol cross-linking is reduced by 12.5%, 14.4% and 9.2% relative to that of MP. Compared with PMP, the graphite structure of GL-PMP, CL-PMP and GA-PMP at 600°C was reduced by 12.0%, 13.9% and 9.0% respectively. Vila et al.

[154] treated flax pulp with laccase / HBT system, and the TG test showed a higher mass loss rate, and the final residual mass was reduced by 6.4% compared with the control. The initial degradation temperature of pulp after phenol cross-linking modification was almost unchanged, and the maximum weight loss temperature was around 370°C. Therefore, although cross-linking modification reduced the residual mass of pulp after combustion, it had little effect on its thermal stability.

[0193] Bioactivity of Enzymatically Cross-linked Modified Fibers

[0194] Inhibitory activity against Vibrio

[0195] The test was conducted using Vibrio fischeri, which is safe for humans. The bacteria is a type of marine luminescent bacteria that can emit blue-green visible light (450-490nm). When the metabolism of the bacteria is inhibited, the luminescence intensity decreases, which can quickly and sensitively reflect the antibacterial activity of the test substance. The fiber before and after modification was made into paper samples to test its effect of inhibiting Vibrio. Figure 8As shown in the figure, the inhibition rate of MP sheets (1 mg paper sheet to 0.5 mL bacterial solution) without XQP bleaching on V.fischeri at 30 min and 60 min was not much different, which were 18.8% and 19.5% respectively. The inhibition rates of GL-MP, CL-MP and GA-MP modified by enzymatic phenol cross-linking on V.fischeri were 39.4%, 21.2% and 24.5% respectively after incubation for 30 min; the inhibition rates after incubation for 60 min reached 43.7%, 44.5% and 41.6% respectively. The inhibition rates of PMP sheets bleached by XQP and immersed in V.fischeri bacterial solution at 30 min and 60 min were 13.0% and 18.0% respectively. After phenol modification, the inhibition rates of GL-PMP, CL-PMP and GA-PMP against V.fischeri were 18.0%, 29.2% and 19.5% at 30 min, and 26.4%, 44.5% and 36.5% at 60 min, respectively. Enzymatic phenol cross-linking modification improved the activity of mechanical pulp in inhibiting Vibrio, and the effect of catechol modification was better than that of guaiacol and gallic acid. In the literature, phenolic compounds grafted onto pulp have antibacterial activity against a variety of microorganisms. For example, Khaldi et al. grafted thymol and carvacrol onto bleached hardwood kraft pulp, which had 40% antibacterial properties against Escherichia coli and Staphylococcus aureus. Fillat et al. grafted syringaldehyde, acetosyringone and p-coumaric acid onto unbleached flax fibers, which almost completely inactivated Staphylococcus aureus, Pseudomonas aeruginosa and Klebsiella pneumoniae. For aquatic products, the risk of Vibrio contamination is high and the harm is great. Many studies have reported the technology of using paper to quickly detect Vibrio. The palm peroxidase-catalyzed phenolic polymerization modified fiber used in the present invention can be used to further develop functional paper products for sanitation and food purposes, such as filter materials for removing Vibrio from water or packaging materials for aquatic products. It should be supplemented that the test data of the present invention are all obtained within 1 hour of incubation. This is because V.fischeri will be largely inactivated after being placed in the test environment for 1 hour, and the data after 1 hour have large errors and low credibility.

[0196] Remove sodium nitrite activity

[0197] The curves of different paper material samples removing NaNO2 are as follows Fig. 9As shown in the figure, the longer the time, the higher the sodium nitrite removal rate. Under normal temperature conditions, MP and PMP can slightly consume sodium nitrite due to the phenolic lignin on their surfaces. After 120 minutes, the sodium nitrite concentration dropped from 0.3 g / L to 0.26 g / L and 0.25 g / L, respectively. After enzymatic cross-linking of phenols, the reaction activity of fibers with sodium nitrite was enhanced, and the effect of cross-linking CL and GA was more significant than that of GL. After 120 minutes, the removal rates of sodium nitrite by CL-MP and CL-PMP were 36.7% and 43.3%, respectively. The mechanical pulp (PMP) treated with XQP had a slightly stronger sodium nitrite removal activity than the untreated mechanical pulp (MP).

[0198] Increasing the temperature is conducive to accelerating the decomposition of sodium nitrite by catechol (CL) modified fibers. Taking CL-MP and its modified fibers as examples, the temperature was raised from room temperature to 50°C and 80°C, respectively. After incubation for 120 minutes, the removal rate of sodium nitrite increased from 13.3% to 70% and 96.7%, respectively. GL-MP and GA-MP are not very sensitive to high temperature, and the activity increase is very small. The PMP series of modified pulps is consistent with the MP series in temperature changes, but the former is slightly less active in removing sodium nitrite than the latter. For example, CL-PMP was incubated at 80°C for 120 minutes and removed 88.3% of the sodium nitrite in the solution. In general, the order of sodium nitrite removal activity given to mechanical pulp by cross-linking different phenols is: catechol> gallic acid> guaiacol.

[0199] Antioxidant activity

[0200] The results of the antioxidant activity (to remove ABTS+ free radicals) of paper samples before and after modification are as follows: Fig.10As shown, GL and CL modified pulps have good scavenging effects on ABTS+· free radicals. GL-MP, GL-PMP, CL-MP and CLPMP were added to ABTS working solution and incubated for 15 minutes, and the scavenging rates all reached more than 88%. After incubation for 30 minutes, almost all ABTS+· free radicals were scavenged. MP and PMP were used as substrates, and the antioxidant activity obtained by crosslinking these two phenols was similar. GA crosslinked pulp had weak antioxidant capacity. The scavenging rates of GA-MP and GA-PMP for ABTS+· free radicals were 56.1% and 64.3% respectively after incubation for 15 minutes, and 65.6% and 75.3% respectively at 30 minutes. Kim et al. crosslinked caffeic acid and mulberry yellow tin to cotton fibers through laccase, and incubated with ABTS+· for 60 minutes. The scavenging rate of ABTS+· free radicals can reach 100%. In comparison, the modified fiber raw material prepared by the present invention has low cost but stronger activity. It is worth mentioning that MP and PMP without phenol modification also have a scavenging rate of 25% (15min) to 40% (30min) on ABTS+· free radicals, and this activity corresponds to the aromatic ring structure of lignin. In fact, in the laccase / ABTS lignin degradation system, ABTS is first oxidized to ABTS+· free radicals, which then act as a mediator to attack the phenolic and non-phenolic structural units of lignin.

[0201] The above are the specific experimental methods and preferred implementations of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.

Claims

1. An antibacterial packaging material, characterized in that: The antibacterial packaging material satisfies at least one of the following conditions: (1) The water contact angle of the antibacterial packaging material is between 27.82±1.58° and 48.79±0.62°; (2) The inhibition rate of the antibacterial packaging material on Vibrio fischeri after incubation for 30 minutes is greater than or equal to 21.2%; (3) The inhibition rate of the antibacterial packaging material on Vibrio fischeri after incubation for 60 minutes is greater than or equal to 41.6%.

2. The antibacterial packaging material according to claim 1, characterized in that: The antibacterial packaging material is obtained by treating eucalyptus mechanical pulp with bio-enzyme-promoted phenols and fiber cross-linking. The eucalyptus mechanical pulp is selected as the pulp that has not been delignified and bleached, recorded as MP pulp; and / or the bleached pulp that has been delignified and bleached, recorded as PMP pulp.

3. The antibacterial packaging material according to claim 2, characterized in that: The antimicrobial packaging material meets at least one of the following conditions: (1) When the eucalyptus mechanical pulp is MP pulp, the antibacterial packaging material prepared by subjecting it to biological enzyme-promoted phenolic and fiber cross-linking modification treatment has an inhibition rate of Vibrio fischeri greater than or equal to 18.0% after incubation for 30 minutes; (2) When the eucalyptus mechanical pulp is PMP pulp, the antibacterial packaging material prepared by subjecting it to a bio-enzyme-promoted phenolic and fiber cross-linking modification treatment has an inhibition rate of Vibrio fischeri greater than or equal to 26.4% after incubation for 60 minutes.

4. The antibacterial packaging material according to claim 2, characterized in that: The biological enzyme is specifically peroxidase extracted from natural palm plants.

5. The antibacterial packaging material according to claim 2, characterized in that: The phenols are specifically at least one of guaiacol, catechol and gallic acid.

6. The antibacterial packaging material according to claim 2 or 5, characterized in that: When the phenol is selected as catechol, the biological enzyme is selected as peroxidase extracted from natural palm plants, and the antibacterial packaging material meets at least one of the following conditions: (a) For the MP pulp of eucalyptus mechanical pulp, the antibacterial packaging material prepared by the peroxidase-promoted catechol and fiber cross-linking modification treatment, after incubation for 120 minutes, the removal rate of sodium nitrite was 36.7%; (b) For the PMP pulp of eucalyptus mechanical pulp, the antibacterial packaging material prepared by the peroxidase-promoted catechol and fiber cross-linking modification treatment, after incubation for 120 minutes, the removal rate of sodium nitrite was 43.3%; (c) for the PMP pulp of eucalyptus mechanical pulp, the antibacterial packaging material prepared by the peroxidase-promoted catechol and fiber cross-linking modification treatment has a reflectivity of no more than 30% in the entire visible region of 400nm-800nm; (d) For the MP pulp of eucalyptus mechanical pulp, the C1 component in the C1 sXPS of the fiber of the antibacterial packaging material prepared by the peroxidase-promoted catechol and fiber cross-linking modification treatment is 52.73%; (e) For the PMP pulp of eucalyptus mechanical pulp, the antibacterial packaging material prepared by the peroxidase-promoted catechol and fiber cross-linking modification treatment has an air permeability of 41.25 μm·Pa-1·s-1; The PMP pulp described in the above conditions (b), (c) and (e) refers to PMP pulp that has been treated with biological enzymes, chelated and bleached with hydrogen peroxide.

7. A method for preparing the antibacterial packaging material according to any one of claims 1 to 6, characterized in that: The steps include: (1) Selecting MP pulp or PMP pulp of eucalyptus mechanical pulp, wherein the acid-soluble lignin content of MP pulp and PMP pulp is 4.1% and 3.0% respectively, and the Klason lignin content is 23.8% and 18.7% respectively; (2) Enzyme-catalyzed fiber surface cross-linking, the specific process includes: Guaiacol, catechol and gallic acid were added to the MP pulp and PMP pulp of eucalyptus mechanical pulp at an amount of 0.05 g / g of absolute dry pulp, and 0.02 g / g of 绝干浆 Peroxidase extracted from natural plants and 0.3 g / L H2O2 were stirred at room temperature for 24 hours; after the reaction was completed, the peroxidase was inactivated by boiling, the unreacted residue was eluted with acetone and washed with deionized water to obtain eucalyptus mechanical pulp MP pulp cross-linked with polyguaiacol, polycatechol and polygallic acid, which were recorded as GL-MP, CL-MP and GA-MP respectively; and eucalyptus mechanical pulp PMP pulp cross-linked with polyguaiacol, polycatechol and polygallic acid were obtained, which were recorded as GL-PMP, CL-PMP and GA-PMP respectively; (3) Sheet making: The slurry obtained in step (2) was heated to 60 ± 1.5 g / m 2 The quantitative sheets are made, and then placed in a constant temperature and humidity chamber for 24 hours. The temperature of the constant temperature and humidity chamber is 23° C. and the relative humidity is 50%. The preparation is now completed.

8. The preparation method according to claim 7, characterized in that: In step (2), the concentration of the MP pulp and PMP pulp of the eucalyptus mechanical pulp is 5%, and they are prepared using a 0.1 mol / L, pH 5.0 phosphate buffer solution.

9. The preparation method according to claim 7 or 8, characterized in that: The biological enzyme is peroxidase, which is extracted from natural plants. The extraction method includes: Preparation of crude enzyme solution Wash with deionized water and drain; weigh 100 leaves of Eryngium scabra, cut the leaves to less than 2 cm, mix with 150 mL of phosphate buffer solution with a concentration of 0.01 mol / L and pH 5, put into a plant wall breaking machine for high-speed wall breaking for 1 min to obtain a homogenate, then filter with 8 layers of absorbent cotton gauze, and then centrifuge for 10 min to remove the filter residue to obtain a clear liquid, which is used as the initial liquid for subsequent separation and extraction, recorded as water extract; slowly drip the water extract into a certain volume of acetone, stir while dripping, stand at 4°C for 15 min, centrifuge for 10 min to remove the supernatant, obtain a precipitate, dissolve the precipitate with phosphate buffer, dilute to 100 mL, and centrifuge again to remove insoluble matter to obtain a crude enzyme solution; Purification of crude peroxidase solution The crude enzyme solution obtained by acetone extraction is pumped into an ion exchange chromatography column to remove pigments and impurities, specifically including: (1) Ion exchanger pretreatment: DEAE cellulose-DE52 was soaked in deionized water for 3 h, soaked in 0.5 mol / L NaOH solution for 30 min, then washed with deionized water until neutral, and then soaked in 0.5 mol / L HCl solution for 30 min and washed again until neutral; (2) Column loading: The pretreated DEAE cellulose-DE52 is loaded into the chromatography column, and the chromatography column is fully equilibrated with a 0.01 mol / L phosphate buffer solution with a pH of 5; (3) Sample loading: 7 mL of crude enzyme solution was added and balanced with 15 mL of phosphate buffer solution; (4) Elution and collection: During elution, 2 mol / L NaCl solution and phosphate buffer solution were used for gradient mixed elution. One tube of sample was collected every 5 minutes. The elution time was 2 hours, and a total of 24 tubes of samples were collected. The peroxidase activity of each tube of sample was detected. (5) Regeneration of the exchanger: Use 1 mol / L HCl and 1 mol / L NaOH for transformation regeneration. If the regenerated ion exchanger is not used for a long time, store it at 4°C to prevent microbial growth; Desalting and freeze drying of peroxidase The enzyme solution after ion exchange chromatography is desalted with an ultrafiltration centrifuge tube, the enzyme solution is placed in the ultrafiltration centrifuge tube, centrifuged at 5000rpm for 10 minutes, the enzyme trapped in the centrifuge tube is dissolved with deionized water, centrifuged again, and the above operation is repeated several times until no Cl- is detected in the centrifuge liquid passing through the filter membrane; finally, the trapped enzyme is dissolved in a phosphate buffer, and freeze-dried into powder with a vacuum freeze dryer to obtain peroxidase; Wherein, in step A, the centrifugation conditions are 4°C, 10000rpm; in step B, the diameter of the chromatography column is 1.6cm and the length is 30cm.

10. An antibacterial packaging material according to any one of claims 1 to 6, used in food packaging, preservation or storage, and / or antibacterial and antioxidant dressings, patches and sheets.